UNATTESTED GREEK WORDS IN THE LIFE OF SAINT GEORGE OF CHOZIBA AND THE MIRACLES OF THE MOST HOLY MOTHER OF GOD AT CHOZIBA - Athanassakis, Apostolos N. (The journal of theological studies, 1994)
APOSTOLOS N. ATHANASSAKIS, TIM VIVIAN; UNATTESTED GREEK WORDS IN THE LIFE OF SAINT GEORGE OF CHOZIBA AND THE MIRACLES OF THE MOST HOLY MOTHER OF GOD AT CHOZIBA,